2022
DOI: 10.1038/s41467-022-32649-7
|View full text |Cite
|
Sign up to set email alerts
|

Transposon-activated POU5F1B promotes colorectal cancer growth and metastasis

Abstract: The treatment of colorectal cancer (CRC) is an unmet medical need in absence of early diagnosis. Here, upon characterizing cancer-specific transposable element-driven transpochimeric gene transcripts (TcGTs) produced by this tumor in the SYSCOL cohort, we find that expression of the hominid-restricted retrogene POU5F1B through aberrant activation of a primate-specific endogenous retroviral promoter is a strong negative prognostic biomarker. Correlating this observation, we demonstrate that POU5F1B fosters the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
3
11
0
Order By: Relevance
“…Although several of them are located in exons and were predicted causing protein sequence changes, none of them actually result in truncated proteins ( Table 1 ). Among these GSSV-related genes, POU5F1B is a great-ape-specific novel gene caused by the retro-position of its mother copy ( OCT4 ) on chromosome 8 (a 1,412-bp INS specifically occurred in the great-ape lineage), confirming the previous report (Simó-Riudalbas et al 2022). Initially, it was thought to be a pseudogene of OCT4 with 95% sequence similarity.…”
Section: Resultssupporting
confidence: 87%
“…Although several of them are located in exons and were predicted causing protein sequence changes, none of them actually result in truncated proteins ( Table 1 ). Among these GSSV-related genes, POU5F1B is a great-ape-specific novel gene caused by the retro-position of its mother copy ( OCT4 ) on chromosome 8 (a 1,412-bp INS specifically occurred in the great-ape lineage), confirming the previous report (Simó-Riudalbas et al 2022). Initially, it was thought to be a pseudogene of OCT4 with 95% sequence similarity.…”
Section: Resultssupporting
confidence: 87%
“…The POU5F1B retrogene is transcribed by activation of upstream transposable element-embedded regulatory sequences in several human solid tumors including colon, stomach, breast, prostate and uterus 1 . Its expression is a negative prognostic factor in colorectal 1 , gastric 2 and hepatocellular 3 malignancies and is associated with advanced histological grades of cervical cancer 4 , where the POU5F1B locus is a papillomavirus integration hotspot 5 .…”
Section: Figurementioning
confidence: 99%
“…The POU5F1B retrogene is transcribed by activation of upstream transposable element-embedded regulatory sequences in several human solid tumors including colon, stomach, breast, prostate and uterus 1 . Its expression is a negative prognostic factor in colorectal 1 , gastric 2 and hepatocellular 3 malignancies and is associated with advanced histological grades of cervical cancer 4 , where the POU5F1B locus is a papillomavirus integration hotspot 5 . Supporting its role as a cancer-promoting factor, the POU5F1B protein stimulates the proliferation of colorectal 1 , gastric 2 and hepatocellular 3 carcinoma cells in vitro and increases the growth 1,2 and metastatic 1 potential of human gastrointestinal tumor cells in mouse xenotransplantation experiments.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…These biomarkers are associated with the altered the phenotypes of CRC cells and play a role in the development and progression of CRC. For example, high expression of the hominid-restricted retrogene POU5F1B in tumor tissues is associated with a poor outcome of patients with CRC and promoted the cancer growth and metastasis by activating intracellular signaling events and releasing trans-acting factors ( Simo-Riudalbas et al, 2022 ). Nowadays, with the deepening of research, recently report has found autophagy proteins have prognostic value for CRC ( Hu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%